Baloxavir marboxil, a novel cap-dependent endonuclease inhibitor potently suppresses influenza virus replication and represents therapeutic effects in both immunocompetent and immunocompromised mouse models - Fukao, Keita (PLoS One, 2019)
Baloxavir marboxil (BXM) is an orally available small molecule inhibitor of cap-dependent endonuclease (CEN), an essential enzyme in the initiation of mRNA synthesis of influenza viruses. In the present study, we evaluated the efficacy of BXM against influenza virus infection in mouse models. Single-day oral administration of BXM completely prevented mortality due to infection with influenza A and B virus in mice. Moreover, 5-day repeated administration of BXM was more effective for reducing mortality and body weight loss in mice infected with influenza A virus than oseltamivir phosphate (OSP), even when the treatment was delayed up to 96 hours post infection (p.i.). Notably, administration of BXM, starting at 72 hours p.i. led to significant decrease in virus titers of >2-log(10) reduction compared to the vehicle control within 24 hours after administration. Virus reduction in the lung was significantly greater than that observed with OSP. In addition, profound and sustained reduction of virus titer was observed in the immunocompromised mouse model without emergence of variants possessing treatment-emergent amino acid substitutions in the target protein. In our immunocompetent and immunocompromised mouse models, delayed treatment with BXM resulted in rapid and potent reduction in infectious virus titer and prevention of signs of influenza infection, suggesting that BXM could extend the therapeutic window for patients with influenza virus infection regardless of the host immune status.